Genetic identification, clinical and epidemiological aspects of an equine infectious anemia outbreak in the Rio Grande do Sul State, Brazil - José Conrado dos Santos Jardim; Paula Fonseca Finger; Grazielle Vieira Cristofari; Bruno Leite Anjos; Carolina Kist Traesel; Mário Celso Sperotto Brum (Ciência Rural, 2023)
ABSTRACT: The study describes the genetic identification, clinical, and epidemiological characteristics of an outbreak of equine infectious anemia occurring in the state of Rio Grande do Sul, Brazil. Three animals kept in the periurban region of Uruguaiana city tested positive for the AGID test. The serology was performed as a requirement for transit. None of the animals showed clinical signs of infection, one animal was necropsied, and the others were stolen. In the post-mortem examination, no macroscopic changes were observed, and microscopically, discrete hemosiderosis was detected in fragments of the liver and spleen. Amplifying and sequencing a proviral DNA fragment in blood, spleen, and mesenteric lymph node samples confirmed EIAV infection. Phylogenetic analysis of the first sequenced EIAV sample from the Rio Grande do Sul State indicates a high similarity with other Brazilian samples. Results confirmed the viral presence in the state’s herds and described epidemiological and virological characteristics of EIA that contribute to the maintenance and dissemination of the virus in herds.